ANALISIS KOMPETENSI PEDAGOGIK GURU PAI DI SEKOLAH DASAR NEGERI SE-KECAMATAN PABUARAN KABUPATEN SERANG - MA’MUR, ILZAMUDIN; HERIANSYAH, DEVI ANGGARA; HILMIYATI, FITRI; WASEHUDIN, WASEHUDIN (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
The aim of this study is to analyze the pedagogical competence of PAI teachers in State Elementary Schools in Pabuaran District, Serang Regency. This research uses a triangulation approach that tests the validity and reality of data in analyzing the pedagogical competence of PAI teachers in State Elementary Schools in Pabuaran District, Serang Regency. By conducting interviews and collecting data which involves analyzing various literary repositories from various literature. The findings of this study show that the pedagogical competence of PAI teachers in State Elementary Schools in Pabuaran District is very good in understanding the characteristics of students, in mastering learning theories and principles, in developing curriculum, in organizing learning, in utilizing technology, in facilitating the development of participants' potential. students, in communicating with students, in carrying out assessments and evaluations, in utilizing the results of assessments and evaluations and carrying out reflective actions to improve the quality of learning. This study also offers a more comprehensive understanding of the importance of pedagogical competence for PAI teachers in State Elementary Schools in Pabuaran District. ABSTRAKTujuan dari studi ini ialah untuk menganalisis bagaimana kompetensi pedagogik guru PAI di Sekolah Dasar Negeri Se-Kecamatan Pabuaran Kabupaten Serang. Penelitian ini menggunakan pendekatan triangulasi yang menguji validitas dan realibitas data dalam menganalisis kompetensi pedagogik guru PAI di Sekolah Dasar Negeri Se-Kecamatan Pabuaran Kabupaten Serang. Dengan melakukan wawancara dan pengumpulan data yang melibatkan analisis berbagai repository sastra dari berbagai literature. Temuan studi ini menunjukan bahwa kompetensi pedagogik guru PAI di Sekolah Dasar Negeri Se-Kecamatan Pabuaran sudah sangat baik dalam memahami karakteristik peserta didik, dalam menguasai teori dan prinsip pembelajaran, dalam mengembangkan kurikulum, dalam menyelenggarakan pembelajaran, dalam memanfaatkan teknologi, dalam memfasilitasi pengembangan potensi peserta didik, dalam berkomunikasi dengan peserta didik, dalam menyelenggarakan penilaian dan evaluasi, dalam memanfaatkan hasil penilaian dan evaluasi dan melakukan tindakan refleksi untuk peninglatan kualitas pembelajaran. Studi ini juga menawarkan pemahaman yang lebih komprehensip tentang pentingnya kompetensi pedagogik bagi guru PAI di Sekolah Dasar Negeri Se-Kecamatan Pabuaran.